SOME PROBLEMATIC ASPECTS REGARDING APPLICATION OF RESTITUTION AND SUBMISSION OF CLASS ACTION IN CASE OF MARKET ABUSE - Fruzerova, Oksana (Teisė, 2016)
Article begins with an analysis of general civil liability provisions regarding compensation of pecuniary damage caused by market abuse activity: insider trading and market manipulation. Further an assessment of two damage compensation mechanisms are being presented: the appropriateness of restitution and the expedience of class action when the pecuniary damage is being caused by market abuse activity. Determination of aggrieved financial market participants and calculation of pecuniary damage is being analyzed. In the end of the article the main findings are presented.